ANALISIS KEUNTUNGAN KIOS BUNGA QUINN FLORIST PADA MASA PANDEMI COVID-19 DI WINANGUN KECAMATAN MALALAYANG KOTA MANADO (Benefits analysis of â€œFlorist Quinnâ€ Flower Stall During the Covid-19 Pandemic in Winangun Kecamatan Malalayang, Manado City) - Joshua Rivaldo Gideon Paat; Jenny Baroleh; Tommy F. Lolowang (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2020)
This study aims to describe and analyze the benefits of the Quinn Florist Flower Kiosk during the Covid-19 Pandemic in Winangun Village, Malalayang District, Manado City. The research took place during July 2020. The data used are primary data obtained from direct interviews with business owners regarding the variables of costs, revenues and profits that occurred during the Covid-19 pandemic and data before the pandemic as a comparison. Data analysis uses profit analysis and to determine the amount and value of interest sales and profits during the pandemic using income analysis. The results showed that the Covid-19 pandemic affected the profits of the Quinn Florist flower stall. The profit obtained before the pandemic period is greater, while during the pandemic period, the profit gained Sales during a pandemic were only part of sales in the pre-pandemic period. In this case, the owner as the owner suffered a loss and almost made the Quinn Florist flower stall owner close his business.Keywords: Benefits analysis, Flower Stall, Covid-19 Pandemic